Magnetometry in Environmental Sciences Studying Environmental Structure Changes and Environmental Pollution (GeoPlanet: Earth and Planetary Sciences,, 2018)
The book offers a review of the work of the Polish Research Group on selected topics of environmental magnetism: the application of magnetic methods to study pollution of outdoor and indoor air, street dust, polluted soil, air filters and indoor dust; the use of magnetic properties to study pedogenic processes in soils and soil structure; as well as deposition processes in recent sediments. The authors focus on detailed cases and provide in-depth explanations of the causes of and relations between physical processes. The examples of different studies demonstrate how to apply magnetometry to solve problems in related disciplines, how to better understand the complexity of the magnetic structure of substances and mediums as well as how to trace interactions between the environment and natural and anthropogenic factors.